Disrupting Australia's vicious VET circle: Sustaining an ITE-qualified VET schoolteacher workforce - O'Reilly-Briggs, Karen; Weller, Jacolyn; Fogelgarn, Rochelle (Issues in educational research, 2025)
An extreme shortage of initial teacher education (ITE) qualified VET schoolteachers impacts the equitable opportunity for young people to become well-educated, vocationally prepared school graduates. This article reports on an international applied research Fellowship designed to discover how Norway and Finland upskill mid-career industry experts to become VET schoolteachers. These countries produce a sustainable VET schoolteacher workforce with approximately half of all upper-secondary students studying VET. In contrast, approximately one-quarter of Australian school students choose VET pathways, at a time when the nation is experiencing a significant skills shortage. We present research findings that illustrate how Norway and Finland produce a sustainable supply of VET secondary schoolteachers. As Australia has yet to develop suitable ITE programs to prepare qualified VET teachers for schools, we argue that Australia would do well to heed Finnish and Norwegian practices that improve the quality of VET in schools, support mid-career industry experts to become VET schoolteachers, and enhance the status of VET in education and society.